Combined creep characterisation from single lap shear tests and 3D implementation for fatigue simulations. (September 2017) - Pin, S.; Frémont, H.; Guédon-Gracia, A.
Abstract: Reliability of electronics is mostly driven by the reliability of lead free solder alloys since the replacement of hazardous materials by RoHS directive. This study aims to combine experiments and finite elements modelling in order to get prepared for fatigue characterisation of complex soldering assemblies. It consists, at first, to identify creep coefficients from experiments and implement them into a numerical model. The model is used to discuss some discrepancies of the results and simulating thermal cycling tests. In a second step, the microstructure of aged specimens is correlated to numerical observations to help finding a proper failure scenario. Highlights: Soldered specimens for shear test have a representative thickness of the electronic applications. Recrystallization is observed in the solder joint after mechanical test and can be compared to BGA specimens after fatigue. A specific creep law combining primary and secondary creep mechanisms is identified using experimental results. Creep law is formulated in a ABAQUS sub routine in order to reproduce shear tests discrepancies.